Effect of Rural Work Environment on Teachers’ Professional Performance in Public Secondary Schools in Ngorongoro, Tanzania - Fatuma Ramadhani Mussa; Michaela Mhagama; Frank Mwamakula (PT. Pusmedia Group Indonesia, 2026)
The rural work environment plays a critical role in shaping teachers’ professional performance, especially in public secondary schools. This study investigated the effect of work environmental in influencing teacher performance in Ngorongoro District. It examined the relationship between rural working conditions and professional outcomes. Using a mixed-methods and a convergent parallel research design, integrating both quantitative and qualitative approaches. Data were collected from 56 respondents: 40 teachers selected through stratified random sampling for questionnaires, 12 teachers purposively selected for interviews, and 4 head teachers selected purposively for interviews, across four rural schools. Data collection involved 40 questionnaires, 12 teacher interviews, and interviews with 4 headteachers. Quantitative data were analyzed using SPSS (Version 25), pearson correlation, and linear regretion. while qualitative data underwent thematic analysis. Findings reveal that, inadequate teaching resources, poor infrastructure, long commuting distances, and limited professional development opportunities negatively impact teachers’ motivation and performance. The study concludes that rural teacher performance is not merely a function of personal dedication but is deeply shaped by systemic environmental conditions. The study confirms a strong relationship between the rural work environment and professional effectiveness, emphasizing the need for targeted policy interventions. Recommendations include improving infrastructure, providing adequate teaching materials, implementing professional development programs, and enhancing teacher well-being to improve performance in rural schools. It also recommends targeted policy interventions: improving infrastructure and teacher housing, ensuring equitable resource distribution, institutionalizing rural-focused professional development, and introducing hardship incentives. Teacher motivation and student outcomes in rural Tanzania will remain compromised without addressing these foundational hygiene factors